Assessment of upper esophageal sphincter function on high-resolution manometry: identification of predictors of globus symptoms - Peng, Lihua; Patel, Amit; Kushnir, Vladimir; Gyawali, C Prakash (Journal of clinical gastroenterology, 2015)
Globus is commonly encountered in clinical practice, but high-resolution manometry (HRM) characteristics are incompletely characterized. We evaluated HRM metrics in globus subjects, compared with age-matched and sex-matched dysphagia subjects and healthy controls. Twenty-four subjects with globus (53.3 ± 2.3 y, 58% female) were compared with 24 age-matched and sex-matched subjects with nonobstructive dysphagia (52.5 ± 2.5 y, 58% female), and 21 healthy controls (27.6 ± 0.6 y, 52% female). Sphincter and segment anatomy, and pressure volume metrics assessed skeletal (proximal contractile integral) and smooth muscle contraction (distal contractile integral). Parameters significantly different across groups on univariate analysis were subjected to multivariate logistic regression and receiver-operating characteristic analysis to identify HRM predictors of globus. Upper esophageal sphincter (UES) postswallow residual pressures were highest in globus (2.6 ± 0.5 vs. 2.3 ± 0.5 mm Hg in dysphagia and 0.6 ± 0.6 mm Hg in controls, P = 0.03); 66.7% had recordable UES residual pressure, in contrast to 9.5% of controls, and 37.5% of dysphagia patients (P = 0.0002). Although different from controls, UES length and basal pressure, and segment 1 parameters did not differ from dysphagia controls. In a multivariate model, measurable UES residual pressure (odds ratio, 6.33; 95% confidence interval, 1.79-25.96) independently predicted globus. Receiver-operating characteristic analysis identified a threshold of 0.4 mm Hg UES residual pressure in segregating globus (sensitivity 66.7%, specificity 71.5%, positive predictive value 55.2%, and negative predictive value 80.0%). HRM with measurement of UES residual pressure allows objective assessment of patients with globus sensation, and has potential to complement current diagnostic strategies.